Access to public transportation and health facilities offering long-acting reversible contraceptives among residents of formal and informal settlements in two cities in Kenya - Veronica Escamilla; Lisa Calhoun; Norbert Odero; Ilene S. Speizer (BMC, 2019)
Abstract Background Despite improved health facility access relative to rural areas, distance and transportation remain barriers in some urban areas. Using household and facility data linked to residential and transportation geographic information we describe availability of health facilities offering long-acting reversible contraceptive (LARC) methods and measure access via matatus (privately owned mid-size vehicles providing public transport) in urban Kenya. Methods Study data were collected by the Measurement, Learning and Evaluation (MLE) Project. Location information for clusters (2010) representative of city-level population were used to identify formal and informal settlement residents. We measured straight-line distances between clusters and facilities that participated in facility audits (2014) and offered LARCs. In Kisumu, we created a geographic database of matatu routes using Google Earth. In Nairobi, matatu route data were publicly available via the Digital Matatus Project. We measured straight-line distance between clusters and matatu stops on 'direct' routes (matatu routes with stop(s) ≤1 km from health facility offering LARCs). Facility and matatu access were compared by settlement status using descriptive statistics. We then used client exit interview data from a subset of facilities in Nairobi (N = 56) and Kisumu (N = 37) Kenya (2014) to examine the frequency of matatu use for facility visits. Results There were 141 (Informal = 71; Formal = 70) study clusters in Nairoibi and 73 (Informal = 37; Formal = 36) in Kisumu. On average, residential clusters in both cities were located ≤1 km from a facility offering LARCs and ≤ 1 km from approximately three or more matatu stops on direct routes regardless of settlement status. Client exit interview data in Nairobi (N = 1602) and Kisumu (N = 1158) suggest that about 25% of women use matatus to visit health facilities. On average, women who utilized matatus travelled 30 min to the facility, with 5% travelling more than 1 hour. Matatu use increased with greater household wealth. Conclusions Overall, formal and informal settlement clusters were within walking distance of a facility offering LARCs, and multiple matatu stops were accessible to get to further away facilities. This level of access will be beneficial as efforts to increase LARC use expand, but the role of wealth and transportation costs on access should be considered, especially among urban poor.